2000
DOI: 10.2337/diacare.23.8.1103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diabetes and mortality: a population study using record linkage.

Abstract: A population study using record linkage O R I G I N A L A R T I C L EOBJECTIVE -To determine patterns and causes of mortality for patients with diabetes in a district health authority.RESEARCH DESIGN AND METHODS -The study used cross-sectional record linkage, combining an electronic death register with a diabetic patient register constructed from a variety of routine health data sources collected from 1991 to 1997. The study was conducted in Cardiff and the Vale of Glamorgan, Wales, U.K., and included all diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 20 publications
8
97
0
3
Order By: Relevance
“…As compared to international data, we find a higher mortality rate (47.9/1000) than in the UK (41.8/1000) [43]. In the US mortality rates for the population aged >65 years are comparable to ours [44].…”
Section: Mortalitysupporting
confidence: 49%
“…As compared to international data, we find a higher mortality rate (47.9/1000) than in the UK (41.8/1000) [43]. In the US mortality rates for the population aged >65 years are comparable to ours [44].…”
Section: Mortalitysupporting
confidence: 49%
“…Combining data from 97 prospective studies, the Emerging Risk Factors Collaboration reported an average of 6 year reduction for a 50-year old with diabetes than a counterpart without diabetes [11]. Morgan et al also reported that life-years lost to diabetes strongly decreased with increasing age at diagnosis [22], and such a trend has been consistent in all reports based on the NHIS data [2,3] including ours.…”
Section: Discussionsupporting
confidence: 79%
“…Some previous studies of other populations also estimated life-years lost associated with diabetes [11,[21][22][23]. Using data from the Framingham Heart Study, Franco et al estimated that men and women 50 years and older with diabetes lived on average 7.5 and 8.2 years less than their equivalents with diabetes, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the mortality experience of the same cohort [40] did suggest that individuals who were invited to screening had a nonsignificant 21% lower mortality (HR 0.79, 95% CI 0.63, 1.00; p00.05) than individuals who were not invited to screening between 1990 and 1999. However, there were relatively few deaths with diabetes noted as an underlying cause (6%); and, although this does not exclude the possibility of coding errors [41], mortality is unlikely to account for the lack of differences between the cases from the screened and unscreened populations.…”
Section: Discussionmentioning
confidence: 99%